Strategic Marketing Plan for OY! Indonesia - Mashayu, Intan; Kartajaya, Hermawan (The Indonesian Journal of Business Administration, 2019)
Abstract. In this digital era, smartphone and mobile application are inseparable parts of human life. With the wider internet accessibility and large population, Indonesia provides the mobile application industry with a very big market. Embracing this opportunity, Jesayas and Jan established OY! in 2016. OY! name is derived from the way Indonesians greet and call others. As a new player, OY! Indonesia is aiming to increase its users’ base and total payment transaction. It offers differentiation for its users by providing payment feature in its chatting room. However, as the players in the industry are significantly increasing, the competition is also getting tougher. Thus, this research is aiming to establish marketing strategy to achieve the goals. The first step is understanding OY!’s current marketing strategies—which consist of segmentation, targeting, positioning, and marketing mix; current customer path; and expected customer path. The following part will gain understanding about external and internal factors affecting OY!’s business. The last part will elaborate proposed marketing strategy and the implementation plan to achieve the expected customer path. The research done has resulted in the strategies to improve OY!’s customer path. The initiatives, which are grouped according to its marketing mix, are already mapped out in the Gantt chart. The implementation of the suggested initiatives will involve all OY!’s employees. This way, OY! is hoped to continuously develop its people, improve internal processes that affect users’ experience and satisfaction, increase performance in every customer touch point, and eventually increase its users’ base and total payment transaction. Keywords: BAR, brand awareness, customer path, marketing metrics, mobile application, PAR, strategic marketing plan